Enacting a Mission for Change: A University Partnership for Young Adolescents - Penny B. Howell; Abigail Deweese; Alice Gnau; Laura Peavley; Caroline Sheffield (Middle Grades Review, 2017)
Abstract As practicing teachers, school personnel, and teacher educators engaged in a school-university partnership, we have worked to co-create a mutually beneficial relationship centered around the learning needs of young adolescents. In this article, we will describe our diverse perspectives on and perceptions of how the partnership enhances the learning experiences of the young adolescents with whom we learn and work. We come to this work with two interrelated goals of preparing a cadre of effective middle grades teachers while improving the educational experiences for 10-14-year-old students at Westport Middle School (WMS)--whether it is through classroom instruction, teacher education, or providing supports within the school.
Keywords: School-university partnerships; clinical teacher preparation; middle school; young adolescents